THE EFFECT OF SELF-REGULATED LEARNING STRATEGY ON WRITING QUALITY OF UNIVERSITY STUDENTS HAVING DIFFERENT COGNITIVE STYLES - Wahyuni, Sri; Pupiales Chuquin, Ector Geovanny; Aini, Nurul (Universitas Muhammadiyah Metro, 2025)
Writing skills are still considered difficult and complex to master by second and foreign language students. Hence, students need to have a good self-regulated learning (SRL) strategy to enhance their writing quality. Furthermore, different types of students' cognitive styles may influence the effect of the SRL strategy used by the students in writing. This article aims to investigate the effect of SRL strategy on the writing quality of students with different cognitive styles. By employing an ex post facto research design, thirty-nine English students joined this study. Direct writing test, SRL questionnaire, and Group Embedded Figure Test (GEFT) were used to collect the data, and simultaneous regression was used to analyze the data. The findings indicate that students' SRL levels and cognitive styles vary, which in turn affects their writing quality. However, the result of the simultaneous regression calculation (0.384) was higher than the significance level (0.05). It means that there was no significant effect of the SRL strategy on the writing quality of students having different cognitive styles simultaneously. Those variables may affect students' writing quality independently. The implication is that EFL instructors should consider individual learner factors independently rather than assuming interaction between SRL and cognitive styles.